PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Zulhaq, Febrinaldi; Media, Afriza; Leni Zahara; Mansurdin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal utilization of technology-based learning media in Natural and Social Sciences (IPAS) instruction at the elementary school level, which causes learning activities to be predominantly teacher-centered, less engaging, and result in low student participation and understanding. Therefore, this research aimed to develop Sparkol Videoscribe-based learning media for Grade V IPAS that meet the criteria of validity, practicality, and effectiveness. This study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The product validity was assessed through expert validation questionnaires involving material experts, media experts, and language experts. The practicality of the media was measured using response questionnaires from teachers and students. The effectiveness of the media was determined based on the comparison of students’ pre-test and post-test results at SDN 24 Batuang Taba as the trial school and SDN 31 Tanjung Aur as the research school. The results showed that the learning media was categorized as very valid, with material validity of 86%, media validity of 86%, and language validity of 94%. The practicality test indicated that the media was very practical, with teacher responses of 91% and student responses of 92% at the trial school, and teacher responses of 94% and student responses of 93% at the research school. The effectiveness test produced N-Gain scores of 0.64 (64%) at the trial school and 0.60 (60%) at the research school, both in the effective category. Thus, the Sparkol Videoscribe-based learning media is valid, practical, and effective for use in IPAS learning in Grade V elementary schools.